Pyroptosis-triggered pathogenesis: New insights on antiphospholipid syndrome - Tan, Yuan; Liu, Qi; Li, Zhongxin; Yang, Shuo; Cui, Liyan (Frontiers in Immunology, 2023)
APS (antiphospholipid syndrome) is a systematic autoimmune disease presenting with the high levels of aPLs (antiphospholipid antibodies). These autoantibodies are involved in various clinical manifestations, mainly including arterial or venous thrombosis formation, proinflammatory response, and recurrent pregnant loss. Pyroptosis is a form of lytic programmed cell death, and it aggravates autoimmune diseases progression via activating NOD-like receptors, especially the NLRP3 inflammasome and its downstream inflammatory factors IL (interleukin)-1β and IL-18. However, the underlying mechanisms of pyroptosis-induced APS progression remain to be elucidated. ECs (endothelial cells), monocytes, platelets, trophoblasts, and neutrophils are prominent participants in APS development. Of significance, pyroptosis of APS-related cells leads to the excessive release of proinflammatory and prothrombotic factors, which are the primary contributors to APOs (adverse pregnancy outcomes), thrombosis formation, and autoimmune dysfunction in APS. Furthermore, pyroptosis-associated medicines have made encouraging advancements in attenuating inflammation and thrombosis. Given the potential of pyroptosis in regulating APS development, this review would systematically expound the molecular mechanisms of pyroptosis, and elaborate the role of pyroptosis-mediated cellular effects in APS progression. Lastly, the prospective therapeutic approaches for APS would be proposed based on the regulation of pyroptosis.